Position-Sensitive Detector in Neutron Tomography and Material Characterization - Idris F.M.; Murshidi J.A.; Mohamed A.A.; Ashari N.; Yazid K.; Azman A.; Wan Abdullah W.A.T.; Norjoharuddeen N.; Baijan A.H.; Sabri R.; Mohd Zin M.F. (Bellwether Publishing, Ltd., 2023)
Neutrons; Optical sensors; Tomography; Axial direction; Highly oriented pyrolytic graphite; Material characterizations; Nanostructural; Neutron cross sections; Neutron detection; Neutron tomography; Position-Sensitive Detectors; Neutron scattering